Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Gula Merah pada Pedagang di Kecamatan Kusan Hulu - Chairani, Tri Buana Tungga Dewi; Ratumbuysang, Monry Fraick Nicky Gillian; Setiawan, Ananda; Bahar, Syaripudin (Universitas Negeri Surabaya, 2024)
The study aims to analyze the marketing strategy of brown sugar sales to traders in Kusan Hulu District. This study uses a qualitative descriptive method. The results showed that the marketing strategies used by respondent 1, respondent 2, and respondent 3 were as follows: 1) The three sellers offered the same product, namely brown sugar without variants, 2) The price offered varied between Rp. 10,000 to Rp. 12,000 per pack, 3) The production site was at home, while marketing was done at home and in the market, 4) Promotion by Ibu Jamah and Ibu Nor Jannah is done by word of mouth, while Ibu Sari Ratna has started using social media as a means of promotion, 5) Each seller provides friendly and good service to consumers, as well as fast and thorough in handling requests, which increases customer satisfaction, 6) Each seller facilitates the ordering and payment process for consumers, 7) Each seller provides an attractive product display to attract the attention of consumers.